Ответы и объяснения

Лучший Ответ!
2014-01-07T19:36:28+00:00
 2^{x+ \sqrt{ x^{2} -4} } -  \frac{5}{2}*   (\sqrt{2}) ^{x+ \sqrt{ x^{2}-4 } } }  -6=0

 2^{x+ \sqrt{ x^{2} -4} } -2.5*  2^{ \frac{x+ \sqrt{ x^{2} -4} }{2} }  -6=0

 2^{ \frac{x+ \sqrt{ x^{2} -4} }{2} } = a      a>0

a²  - 2.5a -6=0
10a² - 25 - 60=0
D = 625 + 2400 = 3025
a₁ = (25+55)/20 = 4
a₂ = (25-55) / 20 =-1.5,  не удов. усл.  a>0

 2^{ \frac{x+ \sqrt{ x^{2} -4} }{2} } = 4 =  2^{2}

x+ \sqrt{ x^{2} -4} = 4
 \sqrt{ x^{2} -4} = 4-x
x² - 4 = 16-8x + x²
8x = 20
x = 2.5
спасибо)
а почему в первой строчке написано 5/2??